Implications for Counselling Asian Transnational Youth: The Experiences of Taiwanese Youth in Vancouver - Petersen, Leah; Park-Saltzman, Jeeseon (Canadian Journal of Counselling and Psychotherapy, 2010)
Using a phenomenological approach, this study sought to explore the long-term psychological impact of families’ transnational separation on children through the lenses of Taiwanese youth in Vancouver. Over time, most participants found themselves in a position of an “ambivalent outsider,” with an increased sense of uncertainty about their identities and future plans. Counselling practices for working with Asian transnational families are discussed.